Evaluating syntactic proposals using minimalist grammars and minimum description length - Ermolaeva, Marina (Journal of Language Modelling, 2023)
Many patterns found in natural language syntax have multiple pos-sible explanations or structural descriptions. Even within the cur-rently dominant Minimalist framework (Chomsky 1995, 2000), it is not uncommon to encounter multiple types of analyses for the same phenomenon proposed in the literature. A natural question, then, is whether one could evaluate and compare syntactic proposals from a quantitative point of view. In this paper, we show how an evaluation measure inspired by the minimum description length principle (Rissa-nen 1978) can be used to compare accounts of syntactic phenomena implemented as minimalist grammars (Stabler 1997), and how argu-ments for and against this kind of analysis translate into quantitative differences.